Monitoring of Water and Solute Transport in the Vadose Zone: A Review - Singh, G. (2020)
A number of contaminants including agrochemicals (fertilizers, pesticides), heavy metals, trace elements, and pathogenic microbes along with pharmaceuticals and hormones used in animal production move through the soil and are responsible for degradation of groundwater quality. Therefore, it is essential to sample soil solution for better understanding of movement and environmental fate of various contaminants in soils. We review different soil solution extraction samplers. The soil solution samplers discussed here are: drainage lysimeter or soil column, pan lysimeter, resin bags or membranes, wick lysimeters, suction cup, and suction plate. We have reviewed 304 journal articles representing a wide array of scientific disciplines. A brief history of soil solution monitoring and terminology used for describing various soil solution samplers is also provided. This review classifies literature on the basis of type of soil solution extraction samplers, soil type, land use–land cover (LULC), and analytes measured. Recommendation criteria are provided for selecting appropriate soil solution extraction samplers based on spatial and temporal variation, cost, soil type, amount of disturbance caused during installation of soil solution samplers, and monitoring of leachates involving different cations, anions, carbon, pH, EC, colloids, pesticides, and microbes. Use of advanced techniques with lysimeters for monitoring soil moisture content, soil water potential and flux is also discussed in this review.